Effect of emulsified absorbent for tar removal in biomass gasification process. Issue 3 (3rd May 2016) - Unyaphan, Siriwat; Tarnpradab, Thanyawan; Takahashi, Fumitake; Yoshikawa, Kunio
ABSTRACT: Tar contained in synthesis gas produced by biomass gasification causes a problem for utilization in downstream applications due to its condensation. According to tar property, it is a complex and various compound hydrocarbons. Some of them are good-dissolved and removed in non-polar substance like oily material while some are in polar substance like water. In this paper, a mixture of water and oil emulsified absorbent, consisting of vegetable oil from canola seed and water without any pretreatment method, is investigated in order to maximize the tar removal performance of both non-polar and polar absorbents. The tar removal performances of the emulsified absorbent and pure vegetable oil were compared by wet and dry tar analysis methods. The results showed that 76.6% of gravimetric tar was removed by pure vegetable oil whereas the best performance was 87.6% of removal in the case of 7.5% emulsified absorbent. For light tar, phenol and naphthalene are mainly trapped due to its high condensation point. For light tar removal, there was no significant difference between pure vegetable oil and 7.5% emulsified absorbent. Therefore, the emulsified absorbent can enhance the gravimetric tar removal performance with no significant change of the light tar removal rate compared with pure vegetable oil.